Research and Development of the High Parameters of Gearbox in Level 4 Centripetal Turbine Power Generation System - Yuan Yongchao; Tao Ye; Chen Yuan; Cao Yanjun; Yu Li; Zhengzhou Research Institute of Mechanical Engineering (Jixie chuandong)
The design,manufacturing and the research and development of high parameter gearbox for generating electricity by utilizing the abandoned residual heat and pressure,residual gas resources of industrial production.